2003
DOI: 10.1080/0266476032000107141
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of some Exponentially Weighted Moving Average methods

Abstract: SUMMARYSeveral versions of the EWMA (Exponentially Weighted Moving Average) method for monitoring a process with the aim of detecting a shift in the mean are studied both for the onesided and the two-sided case. The effects of using barriers for the one-sided alarm statistic are also studied. One important issue is the effect of different types of alarm limits. Different measures of evaluation are considered such as the expected delay, the ARLI, the probability of successful detection and the predictive value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…For small values of 8 it is very slow. However, the use of the asymptotic variance is very common and it can in fact be preferred to the exact version in some aspects, see for example Sonesson (2003). This procedure will be referred to as the "asymptotic version".…”
Section: The Ewma Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For small values of 8 it is very slow. However, the use of the asymptotic variance is very common and it can in fact be preferred to the exact version in some aspects, see for example Sonesson (2003). This procedure will be referred to as the "asymptotic version".…”
Section: The Ewma Methodsmentioning
confidence: 99%
“…Barriers avoid bad properties in the "worst possible" case when the change occurs at a time when the earlier observations least favor the detection of the change. Sonesson (2003) examined the inferential differences between two-sided, one-sided with barrier and ordinary one-sided methods. In this paper we will only deal with ordinary one-sided procedures in order to draw attention to certain optimality issues since optimality is most clearly expressed in this situation.…”
Section: The Ewma Methodsmentioning
confidence: 99%
“…A slight modification of the barriers used in the papers above is used by Morais and Pacheco (1998) to achieve more easily approximated ARL properties. Comparisons between one-and two-sided EWMA with and without barriers with respect to ARL and ED are reported by Sonesson (2001). While the ARL-optimal value of A is zero, as expected, for the one-sided case this is not true for the two-sided one.…”
Section: Two-sided Alternativesmentioning
confidence: 88%
“…However, in a surveillance system the error probabilities are more complicated because of the repeated decisions. A comparison between the EWMAa and the EWMAe methods, for the standard case of Section 3, can be found in Sonesson (2003), where it is concluded that the EWMAa version is preferable for most cases. EWMAe give more frequent alarms at the first time point for the same ARL 0 .…”
Section: Exponentially Weighted Moving Average Methodsmentioning
confidence: 99%